Blood glucose meters and test strips: global market and challenges to access in low-resource settings. Issue 2 (February 2019) - Klatman, Emma Louise; Jenkins, Alicia Josephine; Ahmedani, Muhammad Yakoob; Ogle, Graham David
Summary: Blood glucose meters and test strips for self-monitoring of blood glucose (SMBG) are often inaccessible to, and infrequently used by, people with diabetes in countries with limited resources for health care. Supplies for measuring blood glucose can also be scarce in health facilities, despite being needed in a myriad of clinical settings at all levels of the health system. Numerous studies and international guidelines emphasise the value of SMBG in diabetes care, particularly in people with type 1 diabetes. In this Review, we assess global access to blood glucose meters and test strips, collating published information on cost, availability, system accuracy, competitive bidding, technological trends, and non-financial barriers. We also provide new information on global market share data and prices, taxes and tariffs, and product availability. Blood glucose meters and test strips should be viewed similarly to essential medicines, with issues of access prioritised by relevant international agencies. Efforts are needed to reduce tariffs and taxes and to create unified global system accuracy requirements and accountable post-marketing evaluations. Preferential pricing arrangements, pooled procurement, and best-purchasing practices could help to lower direct costs. SMBG supplies should also be included in national health insurance schemes. Enhanced diabetes education of health professionals and patients is crucial to ensure effective use of SMBG. Finally, as technology advances for people who can afford new interstitial fluid glucose monitoring systems, blood glucose meters and test strips must remain available and become more affordable in low-resource settings.